Decalcification dynamic of dog mineralized tissue by microwaves - Pitol, Dimitrius Leonardo [UNESP]; Issa, Joáo Paulo Mardegan; Caetano, Flávio Henrique [UNESP]; Lunardi, Laurelúcia Orive (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2007)
The aim of this article is to present the decalcification process dynamic of mineralized tissue in dogs, teeth and jaw, comparing the traditional decalcification method, immersion, and microwave, immersion followed by irradiation using a domestic microwave oven, accompanying the liberation of calcium through spectrophotometer of atomic absorption. It was used as decalcified agent, EDTA solution or nitric acid. The results showed that with the use of nitric acid (5%), after 15 days, the irradiated fragments could be processed for histological analysis, otherwise the tooth not irradiated need to be submerged for 65 days. The EDTA decalcified action was slower than the nitric acid. The histological observations of the irradiated samples showed an excellent preservation of the morphological characteristics, independently of the decalcified agent used. © 2007 Sociedad Chilena de Anatomía.
Keywords: Decalcification; Dog; Microwaves; Mineralized tissue; Solution